Nanoparticle sorting in silicon waveguide arrays - Zhao, Haitao (2019)
This paper presents the optical fractionation of nanoparticles in silicon waveguide arrays. The optical lattice is generated by evanescent coupling in silicon waveguide arrays. The hotspot size is tunable by changing the refractive index of surrounding liquids. In the experiment, 0.2-μm and 0.5-μm particles are separated with a recovery rate of 95.76%. This near-field approach is a promising candidate for manipulating nanoscale biomolecules and is anticipated to benefit the biomedical applications such as exosome purification, DNA optical mapping, cell-cell interaction, etc.